Challenges and potentials of forward osmosis process in the treatment of wastewater. Issue 13 (2nd July 2020) - Ibrar, Ibrar; Altaee, Ali; Zhou, John L.; Naji, Osamah; Khanafer, Daoud
Abstract: An emerging osmotically driven membrane process, forward osmosis has attracted growing attention in the field of desalination and wastewater treatment. The present study provides a critical review of the forward osmosis process for wastewater treatment focusing on most recent studies. Forward osmosis is one of the technologies that has been widely studied for the treatment of a wide range of wastewater because of its low fouling and energy consumption compared to conventional techniques for wastewater treatment. To date, forward osmosis has limited applications in the field of wastewater treatment due to several technical and economic concerns. Although membrane cost is one of the critical issues that limit the commercial application of forward osmosis, there are other obstacles such as membrane fouling, finding an ideal draw solution that can easily be recycled, concentration polarization and reverse salt diffusion. Innovative technologies for in-situ real-time fouling monitoring can give us new insights into fouling mechanisms and fouling control strategies in forward osmosis. This study evaluated recent advancements in forward osmosis technology for wastewater treatment and the main challenges that need to be addressed in future research work. Graphical Abstract: Forward osmosis process for wastewater treatment.